2011
DOI: 10.1111/j.1548-1433.2010.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Ancestries, Kinship Connections, and Projected Identities in Four Central Anatolian Settlements: Insights from Culturally Contextualized Genetic Anthropology

Abstract: Previous population genetics studies in Turkey failed to delineate recent historical and social factors that shaped Anatolian cultural and genetic diversity at the local level. To address this shortcoming, we conducted focused ethnohistorical fieldwork and screened biological samples collected from the Yuksekyer region for mitochondrial, Y chromosome, and autosomal markers and then analyzed the data within an ethnohistorical context. Our results revealed that, at the village level, paternal genetic diversity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This result is in agreement with the current knowledge about the genetic structure of the Anatolia peninsula. The Turkish population is an admixture of European, Middle East, and Central Asia ancestries reflecting the gene flows from different Euroasian populations (Cinnioglu et al, ; Gokcumen et al, ; Mergen et al, ; Rootsi et al, ). Specifically, high GSTM1 null frequencies and low GSTT1 null frequencies were observed for Turkish and European populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in agreement with the current knowledge about the genetic structure of the Anatolia peninsula. The Turkish population is an admixture of European, Middle East, and Central Asia ancestries reflecting the gene flows from different Euroasian populations (Cinnioglu et al, ; Gokcumen et al, ; Mergen et al, ; Rootsi et al, ). Specifically, high GSTM1 null frequencies and low GSTT1 null frequencies were observed for Turkish and European populations.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, to the best of our knowledge, no study has reported the distribution of GSTM1 positive/null, GSTT1 positive/null, GSTP1*I105V, and GSTP1*A114V in the Turkish population. The Turkish population is genetically complex due to its demographic history and location near Central Asia, Europe, and the Middle East (Cinnioglu et al, ; Gokcumen et al, ; Mergen et al, ; Rootsi et al, ). As such, reference genetic data for the Turkish population are absolutely mandatory for assessing the reliability of genetic association studies conducted with this population.…”
mentioning
confidence: 99%
“…In contrast to whole‐genome studies, those focusing on maternally inherited mitochondrial DNA or the paternally inherited non‐recombining region of the Y‐chromosome are limited in that they are equivalent to only a single mosaic piece, or locus, even though they can be very informative in studies investigating social organization, kinship connections, or sex‐specific migration patterns (Gokcumen et al. ; Kennett et al. ; Marchi et al.…”
Section: Beyond Europe: a Better Science Of Human Diversitymentioning
confidence: 99%
“…This work has involved populations from Turkey (Gokcumen et al 2011 ), the Caucasus (Sen et al 2014 ), Central Asia (Dulik et al 2011 ;Gokcumen et al 2008 ;Schurr and Pipes 2011 ), and the Altai-Sayan region ( Dulik et al 2012b ). In this chapter, I will review our work with indigenous groups from the Altai-Sayan region ( Fig.…”
Section: Research Questionsmentioning
confidence: 99%